23‐3: High Transparent, Ultra‐thin Flexible, Full color Mini‐LED Display with IGZO TFT substrate. Issue 1 (25th September 2020) - Sun, Yang; Fan, Jack; Yin, Yongming; Liu, Minggang; Jiang, Pei; Zhang, Lijun; Jiang, Bei; Yuan, Chunge; Zhang, Min; Chen, Shu-jhih; Lee, Chia-Yu; Zhang, Xin
Abstract : Mini‐LED and micro‐LED are expected to be the next generation display, due to their diverse applications. In this study, we successfully fabricated an 8‐inch flexible mini‐LED display using an IGZO TFT backplane. Being cooperated with colorless polyimide (CPI) as substrate, the thickness of the mini‐LED panel is less than 0.2mm, and the transmittance is over 60%. The world's first 8‐inch, full color, flexible mini‐LED with IGZO‐TFT backplane is demonstrated.